Global Economic Prospects 2007 : Managing the Next Wave of Globalization - World Bank (Washington, DC: World Bank, 2012)
Global Economic Prospects (GEP) 2007 explores the next wave of globalization. While the medium-term outlook for the world economy remains fairly bright, demographic trends will be a major driver of future events and the benefits of globalization are likely to be uneven across regions and countries. Looking at a set of growth scenarios covering the years 2006 to 2030, the report analyzes the opportunities and stresses of integration in order to bring into sharper relief the choices facing the world today. Three prominent features in the next wave of globalization are: the growing economic weight of developing countries in the international economy, the potential for increased productivity that is offered by global production chains, and the accelerated diffusion of technology. The GEP also analyzes three possible consequences: growing inequality, pressures in labor markets, and threats to the global commons. All of these developments, along with deepening economic interdependence, place a burden on the collective actions of the international community: to manage globalization or risk being run over by it.